Impact of Length of Distal Margin on Outcomes Following Sphincter Preserving Surgery for Middle and Lower Third Rectal Cancers - Bhamre, Rahul (Indian J Surg Oncol, 2019)
Outcomes of sphincter preserving surgery for distal rectal cancers improve with clear circumferential resection and distal resection margin. However, the extent of distal resection margin after a complete mesorectal excision is often a cause for debate. We evaluated the outcome of middle and lower third rectal cancer patients undergoing sphincter preservation with variable distal resection margin at our center. Patients with biopsy-proven rectal adenocarcinoma within 10 cm from anal verge undergoing sphincter preserving resections were included. Patients with positive circumferential resection margin were excluded. Patients were divided into three groups based on the extent of distal resection margin (< 6 mm, 6–10 mm, > 10 mm) and oncological outcomes were compared. The median age of 242 patients was 50 years and 44 (18.2%) were high-grade tumors. Preoperative chemoradiation was used in 185 (75.2%) patients. Median distal resection margin was 20 mm. Patients in < 10 mm group had a significantly higher proportion of lower third (68.3% vs 39.8%, p = 0.004) and chemoradiation-treated tumors (85.4 vs 74.6%, p = 0.001). A significantly higher percentage required an intersphincteric resection in the < 10 mm group (53.7% vs 14.4%, p = 0.0001). Significantly higher percentage tumors were pT3 in > 10 mm group (45.3% vs. 31.7%) (p = 0.05). The median follow-up was 23 months. There was no difference in the overall, loco-regional, and distant recurrence rates between the three groups. A subcentimeter distal resection margin does not influence loco-regional or distant recurrence rates following sphincter preserving surgery for middle and lower third rectal adenocarcinoma.